2021
DOI: 10.5397/cise.2021.00052
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single-dose subacromial injection of a nonsteroidal anti-inflammatory drug in geriatric patients with subacromial impingement syndrome: a randomized double-blind study

Abstract: Background: As nonsteroidal anti-inflammatory drugs (NSAIDs) and steroids have similar effects, steroids can be avoided to reduce adverse effects. This study aimed to compare the differences in symptom improvement after subacromial injection of steroids or NSAIDs.Methods: Sixty patients with rotator cuff syndrome for at least 3 months were enrolled and divided into steroid and NSAID groups. The steroid group received a mixture of 1 mL of triamcinolone acetonide (40 mg/mL) and 1 mL of lidocaine hydrochloride 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…Four studies reported the UCLA as a measure of function as well. Min et al 38 and Kim et al 31 produced ESs in favor of SNIs, large and small, respectively. The papers by Aksakal et al 3 and Yu et al 66 reported ESs for SCIs, moderate and small, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported the UCLA as a measure of function as well. Min et al 38 and Kim et al 31 produced ESs in favor of SNIs, large and small, respectively. The papers by Aksakal et al 3 and Yu et al 66 reported ESs for SCIs, moderate and small, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This could indicate that methylprednisolone is more effective than ketorolac for pain reduction, but less effective for improving function. Meanwhile, in the UCLA analysis, the studies by Min et al 38 and Kim et al 31 also favored SNIs, as seen in the VAS analysis, suggesting that ketorolac is superior to triamcinolone for both pain reduction and improving function. Interestingly, all studies utilizing oxicams 3,30,66 for the CMS or UCLA favored SCIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first treatment of patients should be physiotherapy. While there is no significant difference between the results of patients who undergo physiotherapy and surgery, it is reported that patients should undergo absolute physiotherapy before surgical treatment and surgery should be performed with the correct indication (16,17).…”
Section: Discussionmentioning
confidence: 99%